Pengaruh Kepemimpinan Diri, Pertemanan dan Keterampilan Terhadap Aktualisasi Diri Dalam Kegiatan Olahraga Di Masa Covid-19 - Sepdanius, Endang; Gemaini, Andri; Saputra, Deni; Rifki, Muhamad Sazeli; Afriani, Rini (Jurnal Sporta Saintika, 2023)
This study aims to determine the effect of self leadership, friendship and skills on personal self-actualization in sports activities during the Covid-19 period. This research is a quantitative approach research. The population of this study is the community of Koto Baru District. Researchers took participants who played sports and were willing to become respondents, totaling 123 participants. The assessment instrument is a questionnaire of self-leadership, friendship, and skills and self-actualization in sports activities. Data collection is by giving questionnaires to respondents, through google form and documentation. Data analysis using applications with the Partial Least Square (PLS) method using SmartPLS software version 3. The results obtained in this study indicate that: 1). leadership has no significant effect on self-actualization (t-count < t-table) =1.370 < 1.966707. 2 skills have no significant effect on self-actualization (t-count < t-table) =1.520 < 1.966707. 3) Friendship has a significant effect on self-actualization (t-count> t-table) = 5.620> 1.966707. 4). Friendship has a significant effect on Self Leadership (t-count> t-table) = 16.62> 1.966707. 5). Friendship has a significant effect on Skill Orientation (t-count> t-table) = 6.748> 1.966707.